Beeinträchtigung der Gonadenfunktion nach Chemo- und Strahlentherapie im Kindes- und Jugendalter: Handlungsempfehlungen nach der S1 Leitlinie - Borgmann-Staudt, Anja; Jantke, Andreas; Hinz, Stefan; Beckmann, Matthias; Dittrich, Ralf; Lotz, Laura; Balcerek, Magdalena (Monatsschrift Kinderheilkunde, 2023)
CRIS-Team Scopus Importer:2023-05-26

Determinants of transplantation success with cryopreserved ovarian tissue: data from 196 women of the FertiPROTEKT network - Lotz, Laura; Bender-Liebenthron, J.; Dittrich, Ralf; Häberle, Lothar; Beckmann, Matthias; Germeyer, A.; Korell, M.; Saenger, N.; Kruessel, J. S.; Von Wolff, Michael (Human Reproduction, 2022)
STUDY QUESTION What are the pregnancy and live birth rates for ovarian tissue transplantation and which factors are associated with the success rate? SUMMARY ANSWER Pregnancy and live birth rates per transplanted woman are 32.7% and 26.5% and success rate is associated with female age and first versus repeated transplantation. WHAT IS KNOWN ALREADY Live birth rates after ovarian tissue transplantations have been reported to be between around 24% and 41% per patient. Success rates seem to be negatively associated with increasing female age at the time of tissue cryopreservation and with pelvic radiation. Success rates are apparently not reduced after overnight transportation of ovarian tissue before freezing. STUDY DESIGN, SIZE, DURATION Registry analysis of 244 transplantations in 196 women, performed by 26 FertiPROTEKT network centres from 2007 to 2019 with follow-up till December 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS Orthotopic ovarian tissue transplantations were performed in 196 women, 191 with previous malignant and 5 with previous non-malignant diseases. Size of transplanting centres varied between 1 and 100 transplantations per centre (median: 2). Factors possibly associated with success rate such as female age, first and repeated transplantation, experience of the transplanting centre and overnight transportation of the ovarian tissue before freezing were analysed. MAIN RESULTS AND THE ROLE OF CHANCE Average age of all 196 transplanted women was 31.3 years (SD 5.2; range 17-44) at the time of cryopreservation of tissue and 35.9 years (SD 4.8; range 23-47) at the time of transplantation. Pregnancy rate was 30.6% (95% CI, 24.2-37.6%) per first transplantation and 32.7% (95% CI, 26.1-39.7%) per patient. Pregnancy rate was higher after first transplantation (30.6% (95% CI, 24.2-37.6%)) compared to second and subsequent transplantations (11.8% (95% CI, 3.3-27.5%)). Live birth rate per first transplantation was 25.0% (95% CI, 19.1-31.7%) and per patient 26.5% (95% CI, 20.5-33.3%). Success rate decreased with increasing age at the time of ovarian tissue freezing. Live birth rate was 28.2% (95% CI, 20.9-36.3%) in women <35 years and 16.7% (95% CI, 7.9-29.3%) in women >35 years. Pregnancy rates after first transplantation were higher in centres who had performed >= 10 transplantations (35.1%) compared to centres with <10 transplantation (25.4%) (P = 0.12). Corresponding live birth rates were 27.0% and 18.6%. Success rates were not different in women with and without overnight transportation of tissue before cryopreservation. LIMITATIONS, REASONS FOR CAUTION The data were drawn from a registry analysis. Data such as ovarian reserve and premature ovarian insufficiency were not available for all women. Data might be influenced by different follow-up policies of the centres. WIDER IMPLICATIONS OF THE FINDINGS The study reveals the high potential of ovarian tissue freezing and transplantation, but only if freezing is performed in younger women. The study suggests focus should be placed on the first and not on repeated transplantations. It also opens the discussion of whether transplantation should rather be performed by experienced centres. STUDY FUNDING/COMPETING INTEREST(S) No funding. No competing interests.
CRIS-Team WoS Importer:2022-11-04

Diagnosis, Therapy and Follow-up of Cervical Cancer. Guideline of the DGGG, DKG and DKH (S3-Level, AWMF Registry No. 032/033OL, May 2021) – Part 1 with Recommendations on Epidemiology, Screening, Diagnostics and Therapy - Beckmann, Matthias; Stübs, Frederik; Koch, Martin; Mallmann, Peter; Dannecker, Christian; Dietl, Anna; Sevnina, Anna; Mergel, Franziska; Lotz, Laura; Hack, Carolin; Ehret, Anne; Gantert, Daniel; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Aim This update of the interdisciplinary S3 guideline on the Diagnosis, Therapy and Follow-up of Cervical Cancer (AWMF Registry No. 032/033OL) was published in March 2021. This updated guideline was funded by German Cancer Aid (Deutsche Krebshilfe) as part of the German Guideline Program in Oncology. The guideline was coordinated by the German Society of Gynecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe, DGGG) and the Working Group on Gynecological Oncology (Arbeitsgemeinschaft Gynäkologische Onkologie, AGO) of the German Cancer Society (Deutsche Krebsgesellschaft, DKG). Method The process of updating the S3 guideline dating from 2014 was based on an appraisal of the available evidence using the criteria of evidence-based medicine, adaptations of existing evidence-based national and international guidelines or - if evidence was lacking - on a consensus of the specialists involved in compiling the update. After an initial review of the current literature was carried out according to a prescribed algorithm, several areas were identified which, in contrast to the predecessor version from September 2014, required new recommendations or statements which took account of more recently published literature and the appraisal of the new evidence. Recommendations The short version of this guideline consists of recommendations and statements on the epidemiology, screening, diagnostic workup and therapy of patients with cervical cancer. The most important new aspects included in this updated guideline include the newly published FIGO classification of 2018, the radical open surgery approach for cervical cancers up to FIGO stage IB1, and use of the sentinel lymph node technique for tumors ≤ 2 cm. Other changes include the use of PET-CT, new options in radiotherapy (e.g., intensity-modulated radiotherapy, image-guided adaptive brachytherapy), and drug therapies to treat recurrence or metastasis.
CRIS-Team Scopus Importer:2022-03-04
Keywords: cervical cancer; cervical intraepithelial neoplasia; follow-up; guideline; therapy

Diagnosis, Therapy and Follow-up of Cervical Cancer. Guideline of the DGGG, DKG and DKH (S3-Level, AWMF Registry No. 032/033OL, May 2021) – Part 2 with Recommendations on Psycho-oncology, Rehabilitation, Follow-up, Recurrence, Palliative Therapy and Healthcare Facilities - Fehm, Tanja; Stübs, Frederik; Koch, Martin; Mallmann, Peter; Dannecker, Christian; Dietl, Anna; Sevnina, Anna; Mergel, Franziska; Lotz, Laura; Hack, Carolin; Ehret, Anne; Gantert, Daniel; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Aim This is an update of the interdisciplinary S3-guideline on the Diagnosis, Therapy and Follow-up of Cervical Cancer (AWMF Registry No. 032/033OL), published in March 2021. The work on the updated guideline was funded by German Cancer Aid (Deutsche Krebshilfe) as part of the German Guideline Program in Oncology. The guideline was coordinated by the German Society of Gynecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe, DGGG) and the Working Group on Gynecological Oncology (Arbeitsgemeinschaft Gynäkologische Onkologie, AGO) of the German Cancer Society (Deutsche Krebsgesellschaft, DKG). Method The process used to update the 2014 S3-guideline was based on an appraisal of the available evidence using the criteria of evidence-based medicine, adaptations of existing evidence-based national and international guidelines or - if evidence was lacking - on the consensus of the specialists involved in compiling the update. After an initial review of the current literature was carried out according to a prescribed algorithm, several areas were identified which, in contrast to the predecessor version from September 2014, required new recommendations or statements which would take account of more recently published literature and the recent appraisal of new evidence. Recommendations The short version of this guideline consists of recommendations and statements on palliative therapy and follow-up of patients with cervical cancer. The most important aspects included in this updated guideline are the new FIGO classification published in 2018, the radical open surgery approach used to treat cervical cancer up to FIGO stage IB1, and the use of the sentinel lymph node technique for tumors ≤ 2 cm. Other changes include the use of PET-CT, new options in radiotherapy (e.g., intensity-modulated radiotherapy, image-guided adaptive brachytherapy), and drug therapies to treat recurrence or metastasis.
CRIS-Team Scopus Importer:2022-02-25
Keywords: cervical cancer; cervical intraepithelial neoplasia; follow-up; guideline; therapy

Does it make sense to refreeze ovarian tissue after unexpected occurrence of endometriosis when transplanting the tissue? - Dietl, Anna; Dittrich, Ralf; Hoffmann, Inge; Denschlag, Dominik; Hanjalic-Beck, Aida; Muller, Andreas; Beckmann, Matthias; Lotz, Laura (Journal of Ovarian Research, 2022)
Background: Ovarian insufficiency is a major concern for long-term cancer survivors. Ovarian tissue cryopreservation for fertility preservation is an emerging technique that has proven successful over the past decade through transplantation of frozen-thawed ovarian tissue. Compared to other established techniques, such as oocyte freezing, ovarian tissue cryopreservation preserves actual organ function and thus the production of sex hormones. Endometriosis in perimenopausal women is rare, however it can be surprising diagnosis in the planned transplantation of cryopreserved ovarian tissue and the already thawed tissue may not be transplanted, so that it has to be refrozen. Results: Ovarian function returned in the patient two months after transplantation, as shown by estrogen production. Ten months after the ovarian tissue transplantation mild stimulation with FSH was initiated in accordance with a low-dose protocol. When ultrasonography revealed a follicle 17 mm in size in the ovarian graft, hCG was added and after follicular puncture one oocyte was obtained. The oocyte could be fertilized by IVF and transferred to the uterus. On day 14 after embryo-transfer, a positive hCG-Level was detected and after an uncomplicated pregnancy a healthy child was delivered. Conclusions: We report the first pregnancy and live birth achieved using transplantation of thawed and refrozen ovarian tissue in a woman treated by chemotherapy and subsequent endometriosis surgery. Refreezing of cryopreserved ovarian tissue is not a hindrance to successful transplantation of ovarian tissue. Against the background of increasing numbers of candidates for transplantation of ovarian tissue is expected that the combination chemotherapy followed by endometriosis will increase.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Cancer; Chemotherapy; Cryopreservation; Endometriosis; Fertility preservation; Iatrogenic ovarian failure; Ovarian tissue transplantation; Refreezing

Erratum: Correction to: Fresh and cryopreserved ovarian tissue transplantation for preserving reproductive and endocrine function: a systematic review and individual patient data meta-analysis (Human reproduction update (2022) 28 3 (400-416)) - Khattak, Hajra; Malhas, Rosamund; Craciunas, Laurentiu; Afifi, Yousri; Amorim, Christiani A.; Fishel, Simon; Silber, Sherman; Gook, Debra; Demeestere, Isabelle; Bystrova, Olga; Lisyanskaya, Alla; Manikhas, Georgy; et al. (Human Reproduction Update, 2022)
CRIS-Team Scopus Importer:2022-05-27

Fertilitätserhalt bei onkologischen Erkrankungen im Kindes- und Jugendalter - Lotz, Laura (Pädiatrische Praxis, 2023)
Prior to the implementation of highly gonadotoxic therapies in children and adolescents, counseling on fertility-preserving measures is now obligatory. The consultation should be interdisciplinary and the individual approach requires an estimation of the expected loss of gonadal function taking into account age, pubertal status, therapeutic regimen and general condition. Since some therapeutic options, especially in prepubertal children, are not yet widely established, these measures should be performed only in centers with sufficient expertise in reproductive medicine.
CRIS-Team Scopus Importer:2024-12-16
Keywords: children gonadotoxicity; cryopreservation; fertility preservation; oncological therapy

Fresh and cryopreserved ovarian tissue transplantation for preserving reproductive and endocrine function: a systematic review and individual patient data meta-analysis - Khattak, Hajra; Malhas, Rosamund; Craciunas, Laurentiu; Afifi, Yousri; Amorim, Christiani A.; Fishel, Simon; Silber, Sherman; Gook, Debra; Demeestere, Isabelle; Bystrova, Olga; Lisyanskaya, Alla; Manikhas, Georgy; et al. (Human Reproduction Update, 2022)
BACKGROUND Ovarian tissue cryopreservation involves freezing and storing of surgically retrieved ovarian tissue in liquid or vapour nitrogen below -190 degrees C. The tissue can be thawed and transplanted back with the aim of restoring fertility or ovarian endocrine function. The techniques for human ovarian tissue freezing and transplantation have evolved over the last 20 years, particularly in the context of fertility preservation in pre-pubertal cancer patients. Fresh ovarian tissue transplantation, using an autograft or donor tissue, is a more recent development; it has the potential to preserve fertility and hormonal function in women who have their ovaries removed for benign gynaecological conditions. The techniques of ovarian tissue cryopreservation and transplantation have progressed rapidly since inception; however, the evidence on the success of this intervention is largely based on case reports and case series. OBJECTIVE AND RATIONALE The aim of this study was to systematically review the current evidence by incorporating study-level and individual patient-level meta-analyses of women who received ovarian transplants, including frozen-thawed transplant, fresh or donor graft. SEARCH METHODS The review protocol was registered with PROSPERO (CRD42018115233). A comprehensive literature search was performed using MEDLINE, EMBASE, CINAHL and Cochrane Central Register of Controlled Trials from database inception to October 2020. Authors were also contacted for individual patient data if relevant outcomes were not reported in the published manuscripts. Meta-analysis was performed using inverse-variance weighting to calculate summary estimates using a fixed-effects model. OUTCOMES The review included 87 studies (735 women). Twenty studies reported on >= 5 cases of ovarian transplants and were included in the meta-analysis (568 women). Fertility outcomes included pregnancy, live birth and miscarriage rates, and endocrine outcomes included oestrogen, FSH and LH levels. The pooled rates were 37% (95% CI: 32-43%) for pregnancy, 28% (95% CI: 24-34%) for live birth and 37% (95% CI: 30-46%) for miscarriage following frozen ovarian tissue transplantation. Pooled mean for pre-transplant oestrogen was 101.6 pmol/l (95% CI: 47.9-155.3), which increased post-transplant to 522.4 pmol/l (95% CI: 315.4-729; mean difference: 228.24; 95% CI: 180.5-276). Pooled mean of pre-transplant FSH was 66.4 IU/l (95% CI: 52.8-84), which decreased post-transplant to 14.1 IU/l (95% CI: 10.9-17.3; mean difference 61.8; 95% CI: 57-66.6). The median time to return of FSH to a value <25 IU/l was 19 weeks (interquartile range: 15-26 weeks; range: 0.4-208 weeks). The median duration of graft function was 2.5 years (interquartile range: 1.4-3.4 years; range: 0.7-5 years). The analysis demonstrated that ovarian tissue cryopreservation and transplantation could restore reproductive and hormonal functions in women. Further studies with larger samples of well-characterized populations are required to define the optimal retrieval, cryopreservation and transplantation processes. WIDER IMPLICATIONS Ovarian tissue cryopreservation and transplantation may not only be effective in restoring fertility but also the return of reproductive endocrine function. Although this technology was developed as a fertility preservation option, it may have the scope to be considered for endocrine function preservation.
CRIS-Team WoS Importer:2022-03-11

Ovarian tissue transplantations in 196 women by FertiPROTEKT- live birth rate of 26.5% per woman is associated with female age and first versus repeated transplantation - Lotz, Laura; Bender-Liebenthron, J.; Dittrich, Ralf; Häberle, Lothar; Beckmann, Matthias; Germeyer, A.; Korell, M.; Saenger, N.; Von Wolff, M. (HUMAN REPRODUCTION, 2022)
CRIS-Team WoS Importer:2022-10-21

Predicting mammographic density with linear ultrasound transducers - Behrens, Annika; Fasching, Peter; Schwenke, Eva; Gaß, Paul; Häberle, Lothar; Heindl, Felix; Heusinger, Katharina; Lotz, Laura; Lubrich, Hannah; Preuß, Caroline; Schneider, Michael; Schulz-Wendtland, Rüdiger; et al. (European Journal of Medical Research, 2023)
Background: High mammographic density (MD) is a risk factor for the development of breast cancer (BC). Changes in MD are influenced by multiple factors such as age, BMI, number of full-term pregnancies and lactating periods. To learn more about MD, it is important to establish non-radiation-based, alternative examination methods to mammography such as ultrasound assessments. Methods: We analyzed data from 168 patients who underwent standard-of-care mammography and performed additional ultrasound assessment of the breast using a high-frequency (12 MHz) linear probe of the VOLUSON® 730 Expert system (GE Medical Systems Kretztechnik GmbH & Co OHG, Austria). Gray level bins were calculated from ultrasound images to characterize mammographic density. Percentage mammographic density (PMD) was predicted by gray level bins using various regression models. Results: Gray level bins and PMD correlated to a certain extent. Spearman’s ρ ranged from − 0.18 to 0.32. The random forest model turned out to be the most accurate prediction model (cross-validated R 2, 0.255). Overall, ultrasound images from the VOLUSON® 730 Expert device in this study showed limited predictive power for PMD when correlated with the corresponding mammograms. Conclusions: In our present work, no reliable prediction of PMD using ultrasound imaging could be observed. As previous studies showed a reasonable correlation, predictive power seems to be highly dependent on the device used. Identifying feasible non-radiation imaging methods of the breast and their predictive power remains an important topic and warrants further evaluation. Trial registration 325-19 B (Ethics Committee of the medical faculty at Friedrich Alexander University of Erlangen-Nuremberg, Erlangen, Germany).
CRIS-Team Scopus Importer:2023-10-13
Keywords: Breast cancer risk; Percent mammographic density; Ultrasound

The Hallmarks of Endometriosis Markenzeichen von Endometriose - Psilopatis, Iason; Burghaus, Stefanie; Au, Katharina; Hofbeck, Louisa; Windischbauer, Lisa-Maria; Lotz, Laura; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2024)
A heuristic tool called the hallmarks of cancer helps to reduce the enormous complexity of cancer phenotypes and genotypes to a preliminary set of guiding principles. Other aspects of cancer have surfaced as possible improvements in our understanding of the disease's mechanisms. Endometriosis is a gynecological disease condition negatively impacting the quality of life of many women. To date, there is no curative treatment for endometriosis. Therapy is aimed at treating the symptoms using hormone therapy, pain therapy and complementary therapy. Chronic pain and overlapping pain syndromes and illnesses can also be treated with multimodal pain therapy and psychosomatic therapy. Endometriosis is, however, a chronic and complex entity which, in this regard, resembles cancer. The present work investigates the hallmarks of endometriosis with a view to summarizing the current research status and paving new ways for future research projects.
CRIS-Team Scopus Importer:2024-06-28
Keywords: endometriosis; epigenetics; genetics; molecular; pathway; signaling

Transplantation of refreezed ovarian tissue after unexpected occurrence of endometriosis - Dietl, Anna; Dittrich, Ralf; Hoffmann, Inge; Denschlag, D.; Hanjalic-Beck, A.; Mueller, A.; Beckmann, Matthias; Lotz, Laura (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04